A metabolomic evaluation of the phytochemical composition of tomato juices being used in human clinical trials. (1st August 2017) - Cichon, Morgan J.; Riedl, Ken M.; Schwartz, Steven J.
Highlights: Tomato juices were chemically profiled using LC–MS metabolomics. Phytochemicals belonging to varied compound classes were detected and identified. Greatest differences were in the lipophilic fraction of the tomato juices. Small but significant differences detected in polar phytochemicals. Demonstrates the utility of metabolomics for characterizing foods. Abstract: Juices from the traditional red tomato and a unique tangerine tomato variety are being investigated as health promoting foods in human clinical trials. However, it is unknown how the tangerine and red tomato juices differ in biologically relevant phytochemicals beyond carotenoids. Here liquid-chromatography high-resolution mass spectrometry metabolomics was used to evaluate broadly the similarities and differences in carotenoids and other phytochemicals between red and tangerine tomato juices intended for clinical interventions. This untargeted approach was successful in the rapid detection and extensive characterization of phytochemicals belonging to various compound classes. The tomato juices were found to differ significantly in a number of phytochemicals, including carotenoids, chlorophylls, neutral lipids, and cinnamic acid derivatives. The largest differences were in carotenoids, including lycopene, phytoene, phytofluene, neurosporene, and ζ-carotene. Smaller, but significant, differences were observed in polar phytochemicals, such as chlorogenic acid, hydroxyferulic acid, phloretin-di- C -glycoside, and isopropylmalic acid.